Safety, tolerability, and pharmacokinetics of radavirsen (AVI‐7100), an antisense oligonucleotide targeting influenza a M1/M2 translation - Beigel, John H.; Voell, Jocelyn; Muñoz, Paula; Kumar, Parag; Brooks, Kristina M.; Zhang, Jianbo; Iversen, Patrick; Heald, Alison; Wong, Michael; Davey, Richard T. (British journal of clinical pharmacology, 2018)
Aims The aims of the present study were to assess the safety, tolerability and pharmacokinetics of radavirsen following single ascending doses and multiple doses given as intravenous infusions in healthy adults. Methods A phase I safety and pharmacokinetic study of radavirsen was performed in healthy volunteers. The study was divided into two parts. The first was a single‐ascending‐dose study of five cohorts of eight subjects each, randomized 6:2 to receive single intravenous doses of radavirsen ranging from 0.5 mg kg–1 to 8 mg kg–1 or placebo. The second was a multiple‐dose study of 16 subjects randomized 12:4 to receive 8 mg kg–1 or placebo once daily for 5 days. Results A total of 66 subjects were screened, and 56 subjects were dosed between 2013 and 2015. At least one adverse event occurred in 31/42 (74%) who received radavirsen, and 13/14 (93%) receiving placebo. The most common adverse events were headache and proteinuria, and were similar in incidence and severity among those receiving radavirsen or placebo. Single‐dose pharmacokinetics demonstrated relatively linear and dose‐proportional increases in maximal concentration and in area under the concentration–time curve from zero to 24 h (AUC0–24). At 8 mg kg–1 in the multiple‐dose cohort, the day 4 geometric mean AUC0–24 was 57.9 μg*h ml–1. Conclusion Single infusions of radavirsen up to 8 mg kg–1, and multi‐dosing at 8 mg kg–1 once daily for 5 days, appear to be safe and well tolerated in healthy subjects. The multi‐dose day 4 AUC0–24 in the present study was comparable with that associated with protection from viral infection in a preclinical ferret influenza model. Further evaluation of radavirsen for the treatment of influenza infections is warranted.